Aplikasi Diagnosa Penyakit Pada Tanaman Kelapa Sawit Berbasis Android - Ramadhan, Ahmat Riski; Mustofa, Dimas Ade; Ainuddin, Fadil; Supriyatna, Agiska Ria (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2023)
Efforts to boost oil palm production have so far encountered many obstacles, because every plant that grows has the potential to be threatened by pests and diseases, including oil palm plants. The aggressiveness of this disease most often occurs in seedlings transferred to main nurseries. Consulting someone who is an expert in the industry in terms of problem solving is the best way to get answers, but to find someone who is competent in the field is very difficult especially in rural areas. An application to diagnose oil palm diseases was developed to help detect and control oil palm diseases. This application is a program that can replicate the reasoning of an experienced expert in a particular field of knowledge to solve problems like an expert. This application has a goal to be able to help professionals act as experienced and knowledgeable assistants. Data collection techniques for making this application are carried out by consulting literature studies. With this application, it can help oil palm farmers to take early prevention of diseases that attack their plants.